Inflammatory role of transforming growth factor beta-1 (TGF-β1) in multistep progression of gastric oncogenesis: an immunohistochemical study - Ismail, Ahmad Zharif; Tay, Tan Chow; Samsudin, Nurulhafizah; Azahan, Amir Husaini; Talib, Herni; Hussin, Huzlinda; Ithnin, Hairuszah (International Journal of Pharma Medicine and Biological Science, 2015)
The purpose of this study was to investigate differential expression of TGF-β1 in gastric tissues resected from patients diagnosed with chronic gastritis and gastric cancer (adenocarcinoma) and elucidate the potential role of TGF-β1 in steering towards cancer promoting or cancer suppressing microenvironment. Each group of disease serves as representative model involved in multistep progression of gastric oncogenesis. Immunohistochemistry of TGF-β1 on 162 gastric tissues were performed and analyzed microscopically using semi-quantitative system. Tabulated values which represent each pathological group were then assessed statistically to detect significance of expression. Significance association of expression among groups of age and gender were also included in this study. Chi-square and Mann-Whitney U tests with (p > 0.05) confirmed that TGF-β1 expression was dependent on tissue types and decrement of expression was detected between normal tissues to gastritis and cancer. Higher expression was also observed in diffuse type in comparison to intestinal cancer type. For normal samples, significant difference of expression was found between the two genders; male and female. TGF-β1 have the potential as molecular marker for detecting and monitoring inflamed microenvironment. Expression level in gastric cancer may be target for future therapeutic strategy in preventing cancer progression.